Elementary climate physics - Taylor, F. W. (Oxford University Press, 2005)
Climate Physics is a modern subject based on a space-era understanding of the physical properties of the atmosphere and ocean, their planetary-scale history and evolution, new global measurement systems and sophisticated computer models, which collectively make quantitative studies and predictions possible. At the same time, interest in understanding the climate has received an enormous boost from the concern generated by the realization that rapid climate change, much of it forced by the relentless increase in population and industrialization, is potentially a serious threat to the quality of life on Earth. Our ability to resist and overcome any such threat depends directly on our ability to understand what physical effects are involved and to predict how trends may develop. In an introductory course like that presented here, we want to clarify the basics, topic by topic, and see how far we can get by applying relatively simple Physics to the climate problem. This provides a foundation for more advanced work, which we can identify and appreciate at this level although of course a full treatment requires more advanced books, of which there are many.